2015
DOI: 10.1016/j.cgh.2014.11.028
|View full text |Cite
|
Sign up to set email alerts
|

KRAS and Guanine Nucleotide-Binding Protein Mutations in Pancreatic Juice Collected From the Duodenum of Patients at High Risk for Neoplasia Undergoing Endoscopic Ultrasound

Abstract: BACKGROUND & AIMS Pancreatic imaging can identify neoplastic cysts but not microscopic neoplasms. Mutation analysis of pancreatic fluid following secretin stimulation might identify microscopic neoplasias in the pancreatic duct system. We determined the prevalence of mutations in KRAS and GNAS genes in pancreatic juice from subjects undergoing endoscopic ultrasound for suspected pancreatic intraepithelial neoplasia (PanIN), intraductal papillary mucinous neoplasms, or pancreatic adenocarcinoma. METHODS Secre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 36 publications
5
64
0
Order By: Relevance
“…In comparison, mature pancreatic epithelial cells are mostly refractory to transformation following activation of oncogenic Kras 5. It has also been demonstrated that Kras mutations appear in the pancreas of healthy individuals 6. This supports the hypothesis that oncogenic Kras alone is not sufficient to induce carcinogenesis, and that a transformation-permissive inflammatory environment is prerequisite.…”
Section: Introductionsupporting
confidence: 53%
“…In comparison, mature pancreatic epithelial cells are mostly refractory to transformation following activation of oncogenic Kras 5. It has also been demonstrated that Kras mutations appear in the pancreas of healthy individuals 6. This supports the hypothesis that oncogenic Kras alone is not sufficient to induce carcinogenesis, and that a transformation-permissive inflammatory environment is prerequisite.…”
Section: Introductionsupporting
confidence: 53%
“…KRAS mutations detected in the pancreatic juice of high-risk individuals without pancreatic imaging abnormalities are thought to arise from small PanIN lesions. 15 These studies used digital melt-curve analysis and pyrosequencing to detect mutations but next-generation sequencing (NGS) is being widely used in clinical laboratories to detect somatic mutations in cancer tissues. 1617 …”
Section: Introductionmentioning
confidence: 99%
“…Forty-eight (49.5%) of 97 high-risk patients had a detectable KRAS mutation in their pancreatic juice, including 34 (53.1%) of 64 with and 14 (42.4%) of 33 without cysts suspected to be IPMN, a prevalence very similar to what we reported previously in this population. 17 Patients with KRAS mutations in their pancreatic juice were older on average than those without a KRAS mutation ( P = 0.056). Thirty-six of 106 patients (34.0%) with cysts suspected to be IPMN had GNAS mutation s detected in their pancreatic juice.…”
Section: Resultsmentioning
confidence: 98%
“…3, 4, 9 Studies using these samples revealed that GNAS mutations detected in pancreatic fluid samples collected from the duodenum are highly correlated with the presence of IPMN, that KRAS mutations are commonly detected in pancreatic fluid samples of patients who are undergoing screening for their family history of pancreatic cancer and that mutation concentrations as well as mutations that are known to arise in high-grade dysplasia and invasive cancer such as in SMAD4 are helpful in distinguishing the presence of pancreatic ductal adenocarcinoma. 12, 14, 16, 17 Since secretin-stimulated pancreatic fluid samples are typically collected from the duodenal lumen, they are admixed with abundant wild-type DNA in duodenal fluid effectively reducing mutation concentrations. 18 The very low concentrations of mutations typically found in these duodenal collections requires that more sophisticated molecular tools be employed for their detection.…”
Section: Introductionmentioning
confidence: 99%